Low temperature decreased insecticidal protein contents of cotton and its physiological mechanism - Chen, Yuan; Liu, Zhenyu; Dai, Yuyang; Yue, Ye; Liu, Yuting; Li, Hanjia; He, Run; Zhang, Xiang; Chen, Dehua (Frontiers in Plant Science, 2023)
Low temperature delayed cotton growth, increased abscission of reproductive organs, and seriously reduced quality and yield. Moreover, failed or unstable performance of insecticidal resistance due to adverse environments have been reported. In order to study the impact of low temperature on the insecticidal protein contents at square stage in Bacillus Thuringenesis (Bt) transgenic cotton, different temperature regimes and durations were imposed on two Bt cotton cultivars, Sikang1 (the conventional cultivar, SK1) and Sikang3 (the hybrid cultivar, SK3). Low temperature stress exhibited a significant inhibitory effect on insecticidal protein expression in squares and leaves of Bt transgenic cotton plants, with insecticidal protein contents decreased up to 30% with decreasing temperature. In addition, the threshold temperature resulting in significant reduction of insecticidal protein contents symbolized a rising trend as stress duration extended, together with a greater reduction observed. Thus, at square stage, the detrimental influence of low temperature on Bt protein contents was closely related to the low temperature level and duration. The square Bt protein content was positively correlated with leaf Bt protein content, but was more sensitive to low temperature. Across the whole treatment duration in both years, square Bt protein level was significantly negatively correlated with malondialdehyde (MDA) contents, as well as the activities of catalase (CAT) and superoxide dismutase (SOD), indicating the negative effect of cold induced oxidative stress on Bt protein contents. The reduced Bt protein contents under low temperature were also related to altered N metabolism. Glutamate oxaloacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT) activities, as well as soluble protein contents in squares reduced, and greater reduction was recorded with decreasing temperature. In contrast, the free amino acid contents, and peptidase and protease activities increased, and greater elevation was noted with decreasing temperature. These results suggested in Bt cotton production, it is necessary to be alert to low temperature disasters that may last for more than 24 hours and lower than 15-17°C during the square stage, which may lead to reduced insecticidal resistance causing serious economic losses.